Cryoglobulin interference in laboratory tests: analytical error or diagnostic clue? - Pandashina Masabanda, Angel Isaias (2025)
Cryoglobulins are immunoglobulins that precipitate at low temperatures and redissolve upon reheating the sample. They are also a well-known source of laboratory test errors, potentially compromising medical diagnosis. This review aimed to analyze cryoglobulin interference in clinical laboratory tests to determine whether it represents merely an analytical error or a valuable diagnostic clue. A literature review was conducted using scientific databases from 2020 to 2024. Notably, their presence has often been crucial in identifying pathologies that are difficult to diagnose. In conclusion, the detection of cryoglobulins in clinical samples should not be regarded solely as an analytical error but also as a valuable diagnostic indicator of underlying diseases that are often challenging to detect by other means.